Trilingual Education in Kazakhstan: Motivation and Attitude of Science Teachers in Learning English - Saule Polatova; Alima Nurlybekova; Dildar Kistaubaeva (European Scientific Journal, ESJ, 2019)
The purpose of the article is to investigate the integrative and instrumental motivation and attitude ofschoolscience teachers involved in the process of learning English. A survey was conducted with school science teachers who were undertaking training at the Shymkent branch of Orleu, the national center for the in service training of teachers in South Kazakhstan. From the "State Program for Education Development in the Republic of Kazakhstan for 2011- 2020", it became mandatory for school science teachers to teach through the medium of English, according to the national policy on trilingual education (Ministry of Education and Science of the Republic of Kazakhstan, 2010, p-2). The study involved 117 school science teachers (teaching Chemistry, Biology, Physics, and Computer Science): 18 males and 99 females from aged between twenty and sixty years old. Questionnaire data was collected through twenty items adapted from a five-point Likert scale. The statistical results from the survey data on the measurement of instrumental and integrated motivation were measured by SPSS and Excel. The results showed that school science teachers had a high level of motivation, both integrative and instrumental, for learning English; but instrumental motivation was slightly higher than integrative motivation. Data analyses on the main difficulties in learning English show that there is no language environment where teachers and indeed the wider population can develop their language skills.